Youth Mentoring: Involving College Students - Emily Rickerson; Muthusami Kumaran; Kate Fogarty (EDIS, 2011)
Today’s youth are facing a number of troubling issues including substance abuse, family disturbances, bullying, low morale resulting in low academic achievement, dropping out of school, and more. Having someone who cares about youth, to talk to them about the issues they face and mentoring them, can be a positive factor for all involved. This 3-page fact sheet was written by Emily Rickerson, Muthusami Kumaran, and Kate Fogarty about a collegiate mentor service learning program at the University of Florida., and published by the UF Department of Family Youth and Community Sciences, August 2011. (Photo © C.A.M.P. Gator)